ANALISIS PENGARUH PENGELUARAN PEMERINTAH DI SEKTOR PENDIDIKAN, SEKTOR KESEHATAN, SEKTOR INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (PERIODE TAHUN 2010-2017) - Jofani Mega Puspitasari; Sudati Nur Sarfiah; Rusmijati . (DINAMIC : Directory Journal of Economic, 2019)
This study aims to determine the effect of government spending in the education sector, health sector, infrastructure sector  on  Indonesia's  economic  growth.  This  research  is  classified  as  associative  quantitative research. The data analysis method used in this study is a multiple linear regression analysis tool with the help of Statistical Package for Solution Solution (SPSS). The data in this study used Indonesian secondary data from 2010 to 2017. The statistical tests in this study used the classic assumption test including (normality test, heteroscedasticity test, multicollinearity test autocorrelation test), t test, f test, and test R2. The results showed that: 1.  Variables  of  government  expenditure  in  the  education  sector  partially  showed  a  positive  and  significant nfluence on economic growth in Indonesia. 2. Variable government expenditure in the health sector partially shows a positive and significant influence on economic growth in Indonesia. 3. Variable government expenditure in the infrastructure sector partially shows a positive and significant influence on economic growth in Indonesia. 4. Variable government expenditure in the education sector, health sector, infrastructure sector together have a significant influence on economic growth in Indonesia. Keywords: Government Expenditures, Education, Health, Infrastructure, Economic Growth.